2003
DOI: 10.3168/jds.s0022-0302(03)73732-1
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Parameters for Milk Somatic Cell Scores and Relationships with Production Traits in French Lacaune Dairy Sheep

Abstract: Records from 94,445 and 45,499 French Lacaune dairy ewes in first and second lactations, respectively, were used to estimate genetic parameters for somatic cell scores. Somatic cell count data came from an extensive recording scheme and sample testing that began in 1999 using the flocks enrolled in the official milk recording system. Somatic cell count data were from 2 to 4 test days per lactation. Lactation average and single test-day somatic cell scores were considered in multitrait sire models. The heritabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
45
1
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(56 citation statements)
references
References 21 publications
(36 reference statements)
6
45
1
4
Order By: Relevance
“…Heritability estimates, based on repeatability test-day models, range from 0.04 to 0.16 for several breeds including the Churra (Baro et al, 1994;El-Saied et al, 1998;Othmane et al, 2002), the Manchega (Serrano et al, 2003), the East Friesian (Hamann et al, 2004) and the Valle del Belice sheep breeds (Riggio et al, 2007). Other studies reported similar or slightly higher heritability estimates (from 0.11 to 0.18) for the average SCS during lactation, for Chios (Mavrogenis et al, 1999), Lacaune (Barillet et al, 2001;Rupp et al, 2003a), Latxa (Legarra and Ugarte, 2005) and Manech Red Faced ewes (Barillet et al, 2008). These heritability estimates are comparable to those reported in literature for cattle either with test-day (Carnier et al, 1997;Mrode et al, 1998) or lactation models (Rupp and Boichard, 1999).…”
Section: Genetic Parameters Of Scc and Mastitis In Sheepmentioning
confidence: 66%
“…Heritability estimates, based on repeatability test-day models, range from 0.04 to 0.16 for several breeds including the Churra (Baro et al, 1994;El-Saied et al, 1998;Othmane et al, 2002), the Manchega (Serrano et al, 2003), the East Friesian (Hamann et al, 2004) and the Valle del Belice sheep breeds (Riggio et al, 2007). Other studies reported similar or slightly higher heritability estimates (from 0.11 to 0.18) for the average SCS during lactation, for Chios (Mavrogenis et al, 1999), Lacaune (Barillet et al, 2001;Rupp et al, 2003a), Latxa (Legarra and Ugarte, 2005) and Manech Red Faced ewes (Barillet et al, 2008). These heritability estimates are comparable to those reported in literature for cattle either with test-day (Carnier et al, 1997;Mrode et al, 1998) or lactation models (Rupp and Boichard, 1999).…”
Section: Genetic Parameters Of Scc and Mastitis In Sheepmentioning
confidence: 66%
“…These are still a matter of discussion, as estimates in the Lacaune breed are unfavourable, whereas estimates in the Spanish breeds are favourable (e.g. Rupp et al (2003) and Legarra and Ugarte (2005) and references therein) but we have shown that for different estimates either economic weights or a desired gains index are adequate, the latter being slightly economically worse. Yet one needs to be careful not to set too strong a restriction for the change in SCS, because the risk of greatly diminishing gains for milk yield exists depending on the true genetic parameters.…”
Section: Discussionmentioning
confidence: 86%
“…Legarra and Ugarte (2005) estimated in the Latxa breed heritabilities of 0.21 for milk yield and 0.13 for SCS, and a (favourable) genetic correlation of 20.30. Rupp et al (2003) estimated in the Lacaune breed a genetic correlation that turns out to be unfavourable (between 0.08 and 0.18). The pseudo-economic weight was calculated to fix, under these conditions, the genetic change of SCS to zero.…”
Section: Sensitivity Analysismentioning
confidence: 98%
See 1 more Smart Citation
“…Sub-clinical mastitis is generally diagnosed by an increase in somatic cell counts (SCC) in the milk. Although heritability for mastitis (,0.04) and SCC (0.11) in dairy cattle is low, the genetic correlation between the two is high (,0.70), so that SCC can be conveniently used in selection index to reduce the incidence of mastitis in cows (Mrode et al, 1998;Heringstad et al, 2000;Colleau and Regaldo, 2001;Willam et al, 2002) and ewes (Barillet et al, 2001;Rupp et al, 2003). These examples show the potential of genetic selection and significant progress may be made by the exploration of the molecular polymorphism responsible for these genetic effects on susceptibility to disease.…”
Section: Introductionmentioning
confidence: 99%